2022
DOI: 10.7717/peerj.13993
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the distribution and fine-scale habitat selection of mesocarnivores along a habitat quality gradient in western Himalaya

Abstract: Background: Human activities have resulted in a rapid increase of modified habitats in proximity to wildlife habitats in the Himalaya. However, it is crucial to understand the extent to which human habitat modification affects wildlife. Mesocarnivores generally possess broader niches than large carnivores and adapt quickly to human activities. Here, we use a case study in the western Himalaya to test the hypothesis that human disturbance influenced mesocarnivore habitat use. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 108 publications
0
2
0
Order By: Relevance
“…Conversely, other studies, such as Mohamed et al [ 47 ] and Wu et al [ 19 ], found that leopard cats had a strong tendency to use and adapt to habitats near areas of human settlement. Whereas, wildlife will also shift their habitat selection due to habitat modification [ 23 ]. In the present study, we found the site-use of the diurnal squirrels and the nocturnal rats was strongly influenced by the forest cover and aspect, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, other studies, such as Mohamed et al [ 47 ] and Wu et al [ 19 ], found that leopard cats had a strong tendency to use and adapt to habitats near areas of human settlement. Whereas, wildlife will also shift their habitat selection due to habitat modification [ 23 ]. In the present study, we found the site-use of the diurnal squirrels and the nocturnal rats was strongly influenced by the forest cover and aspect, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This cat often uses opportunistic feeding strategies and exhibits plasticity in its habitat use and temporal activity to accommodate to habitat modification. For example, leopard cats may show a shift in habitat selection from their natural habitat to highly disturbed areas [ 23 ], and exhibit different diel activity among habitats and across seasons [ 24 , 25 ], including nocturnal-crepuscular activity [ 8 , 26 ], or even arrhythmic activity [ 27 , 28 ]. The plasticity of habitat use and temporal activity by leopard cats can optimize the exploitation of a diverse range of nocturnal and diurnal prey.…”
Section: Introductionmentioning
confidence: 99%